Trans Fatty Acid Biomarkers and Incident Type 2 Diabetes: Pooled Analysis from 10 Prospective Cohort Studies in the Fatty Acids and Outcome Research Consortium (FORCE) (OR33-02-19). (13th June 2019) - Lai, Heidi; Imamura, Fumiaki; Korat, Andres Ardisson; Murphy, Rachel; Tintle, Nathan; Bassett, Julie; Chen, Jiaying; Kröger, Janine; Forouhi, Nita; Schulze, Matthias; Harris, William; Ramachandran, Vasan; et al.
Abstract: Objectives: To assess prospective association between circulating biomarkers of individual trans fatty acids (TFAs) and incident type 2 diabetes (T2D) in diverse populations. Methods: A harmonized analysis of individual level data was conducted for TFA biomarkers and incident T2D by pooling ten prospective cohort or nested-case-control studies from five countries (Australia, Germany, Iceland, UK, and USA). Fatty acids (FAs) were measured in plasma phospholipid, red blood cell membrane phospholipid, or total plasma collected between 1990–2008 from 22, 711 participants aged ≥18 years without prevalent diabetes. Evaluated TFAs included trans -16:1n-9, sum of trans -18:1 isomers ( trans -18:1n6 to trans -18:1n12), sum of trans -18:2 isomers ( cis/trans -18:2, trans/cis -18:2, trans/trans -18:2), and individual trans -18:2 isomers. The multivariable-adjusted relative risk or odds ratio was estimated in each cohort by lipid compartments using a pre-specified protocol for definitions of exposures, covariates, and outcomes for statistical analysis. Association estimates were pooled using fixed-effects inverse-variance weighted meta-analysis. Results: During an average maximum of 14 years of follow-up, 2244 cases of incident T2D were identified. Median levels of TFAs across cohorts were 0.05–0.18% total FAs for trans -16:1n-9, 0.09–2.05% for total trans -18:1, 0.10–0.73% for total trans -18:2, and 0.01–0.36% for individual trans -18:2 isomers. In overall pooled analysis, TFAs evaluated per inter-quintile range were not significantly associated with risk of T2D (Figure 1). Findings were consistent when TFAs were assessed categorically in study specific-quintiles, and when associations were pooled within lipid compartment (i.e., phospholipids vs. total plasma). Conclusions: Overall, biomarker levels of TFAs were not significantly associated with risk of incident T2D in this international pooling project. Findings may be due to mixed TFA sources (industrial vs. ruminant), a general decline in TFA exposure during this period, or no effect of circulating TFA on diabetes. Associations of TFA biomarkers with T2D at higher exposures should be investigated. Funding Sources: See Table 1. Supporting Tables, Images and/or Graphs: